Histological analysis of different local haemostatic agents used for periapical surgery: An experimental study with Sprague- Dawley rats - Mena Álvarez, Jesús; Quispe López, Norberto; Zubizarreta Macho, Álvaro; Rico Romano, Cristina; Rodero Villanueva, Rosa; Fernández Aceñero, María Jesús (My University, 2019)
The aim of the present study was to analyse differences in the tissue response to the different haemostatic agents used for periapical surgery (BloodSTOP iX® (oxicellulose), Expazen® (aluminum chloride), calcium sulphate (CS), Gelatamp ® (gelatin sponge) and Hemocor® (ferric sulphate). Seventy-two bone defects were made on the calvarium of 36 Sprague-Dawley rats. The specimens were euthanised at 3, 6 and 12 weeks. Histological analysis revealed a giant cell foreign body reaction against BloodStop iX®, Gelatamp® and Hemocor®. Leukocytes persisted at the surgical bed during the healing process longer as expected with Gelatamp® (6 weeks) and Hemocor® (12 weeks). We confirmed a generalised delay in bone formation. Calcium sulphate did not cause any foreign body reaction. CS showed excellent results with a high degree of compatibility, there was no inflammatory reaction with this agent after 12 weeks and was not associated with a significant foreign body reaction at any time during the study.